PENGAJARAN SHOLAT PADA ANAK USIA DINI PERSPEKTIF HADIS NABI MUHAMMAD SAW - Risdianto Hermawan (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Early age is the golden age or the golden age. In this phase, the child can absorb all the knowledge gained in the surrounding environment to the maximum. At this age, the planting of religious values ​​must be carried out continuously, so that it will become a child's habit. Based on observations in the environment, today's children seem to be proud or reluctant to pray in congregation in the mosque, which we can observe when the child has reached puberty around middle school age, the child will stop reciting. All of this depends on the environment and education experienced at an early age. Problems like this often occur in various regions, children are reluctant to pray. Some influencing factors include factors in the child and environmental factors. This paper describes the method of teaching children to pray early on according to the hadith of the Prophet Muhammad and the level of early childhood development, including; exemplary, habituation, advice, attention and monitoring, and punishment. Keywords: Sholat, Anak Usia Dini, Hadis Nabi.